The effect of Bifidobacterim bifidum cell-free supernatants, ascorbic acid, fructose, sorbitol, xylitol and stevia on the daily biomass growth of opportunistic microorganisms - Knysh, O; Martynov, A (Annals of Mechnikov's Institute, 2020)
Introduction. The use of probiotic bacteria as biotransformator system is a promising way to obtain new derivatives of known substances with antimicrobial or other beneficial activity. The aim of the research was to investigate the effect of the Bifidobacterim bifidum cell-free supernatants, obtained by cultivation of bifidobacteria in their own disintegrate supplemented with ascorbic acid (BbAsc), fructose (BbFr), sorbitol (BbSor), xylitol (BbXyl) or stevia (BbSt) and the substances themselves (Asc, Sor, Xyl or St) on the growth of opportunistic microorganisms. Material & methods. The effect of the studied supernatants and substances on the daily biomass growth of the test cultures was investigated by spectrophotometry using a 96-well polystyrene microtiter plates and a «LisaScanEM» spectrophotometer («ErbaLachemas.r.o.», Czech Republic). Reference strains Staphylococcus aureus ATCC 25923; Escherichia coli AТСС 25922 and Pseudomonas aeruginosa AТСС 27853 were used as a test cultures. The final concentration of the studied supernatants and substances in the incubation medium was 30%vol, and the final concentration of bacterial cells was ~106 CFU/ml. Inhibition (II) or stimulation (SI) indices of the daily biomass growth of test cultures were calculated by the formula where ∆Dt and ∆Dc are the optical density gain of test and control samples. Results & discussion. Among the studied substances, stevia alone did not affect the daily biomass growth of any of the test cultures, either as in solution with a final concentration of 30 mg/ml or as in a supernatant of B. bifidum culture. Fructose at a final concentration of 30 mg/ml had the same effect on test cultures growth as the supernatant of B. bifidum culture after probiotic cultivation with fructose: it inhibited staphylococcal growth (Fr: II = 30,9 %, BbFr: II = 34,6 %), stimulated the growth of P. aeruginosa (Fr: ІS = 23,7 %, BbFr: IS = 19,8 %) and did not affect the growth of E. coli. Xylitol at a final concentration of 30 mg/ml did not affect the growth of P. aeruginosa biomass, but inhibited the growth of E. coli (ІI = 20,9 %) and S. aureus (ІI = 28,4 %). The supernatant of B. bifidum, cultured in the presence of xylitol inhibited the growth of S. aureus biomass (ІI = 26,1 %) and did not affect the growth of the other test cultures. The sorbitol and cell-free supernatant of B. bifidum cultured in the presence of this polyol equally influenced the biomass growth of test cultures: had no significant effect on the daily biomass growth of S. aureus but stimulated the growth of E. coli (BbSor: ІS = 43,9 %, Sor: ІS = 34,5 %) and P. aeruginosa (BbSor: ІS = 26,4 %, Sor: ІS = 28 %). The only substance that significantly inhibited the biomass growth of all test cultures was ascorbic acid. Cell-free supernatant of B. bifidum (BbAsc) cultured in disintegrate supplemented with ascorbic acid caused more pronounced inhibition of the daily biomass growth (S. aureus – 78 %, E. coli – 52 % and P. aeruginosa – 45 %) compared to ascorbic acid (Asc) itself (S. aureus – 42 %, E. coli – 35 % and P. aeruginosa – 38 %). Conclusion. Among the studied substances, only ascorbic acid caused significant inhibition of biomass growth of all test cultures. B. bifidum sell-free supernatant obtained by cultivation of bifidobacteria in their own disintegrate supplemented with ascorbic acid caused a more severe inhibition of test cultures growth than ascorbic acid itself. The absence of signs of chemical modification of ascorbic acid in the B. bifidum cell-free supernatant on the chromatogram indicates that the greater inhibitory effect of this supernatant is due to the synergistic effect of ascorbic acid and the inhibitory compounds produced by B. bifidum during cultivation. The other studied substances showed various effects on the daily biomass growth of test cultures. The use of B. bifidum as a biotransformer system, and xylitol, sorbitol, fructose and stevia as precursors for the production of new antimicrobials by combinatorial biosynthesis, turned out to be not effective enough. DOI: 10.5281/zenodo.3885190